An AHP-Bayesian Model for Operational Risk Evaluation of Integrated Energy Systems. (March 2019) - Yang, Yongqi; Xue, Wanlei; Li, Chaoyuan; Zhao, Xin; Xu, Nan
Abstract: The rapid development of Integrated Energy Systems (IES) is of great significance in solving the increasingly serious environmental problems by promoting China's energy evolution. Under the huge policy support, China's IES technology has taken a great-leap-forward development. Meanwhile, a large number of IES projects will be carried out extensively. Therefore, operational risk evaluation for IES projects is of great urgency. In the first place, we will summarize the basic structure of IES and build operational risk evaluation index system for IES projects based on characteristics of China's IES systems Secondly, the improved Bayesian operational risk evaluation model will be established. In this improved model, AHP method will be used to calculate the weight of every index. Last but not least, a case study is implemented to prove the practicality of the model and provide references for the IES projects decision and optimization.